Peningkatan Kemampuan Membaca melalui Kartu Bergambar dengan Model PBL Pelajaran Bahasa Indonesia di Sekolah Dasar - Nur Rohmah, Ellyna; Desstya, Anatri; Artik (Universitas Muhammadiyah Kotabumi, 2024)
One of the fundamental skills that students must have is reading. By having reading skills, students can participate in and comprehend learning effectively. However, in reality, many students, especially in grade 1, cannot read yet. This study aims to improve the reading ability of grade 1 students at SD Muhammadiyah Plus Malangjiwan through picture card media using the PBL model. The subjects of this study were 19 grade 1 students at SD Muhammadiyah Plus Malangjiwan in the academic year 2023/2024. Data collection techniques included interviews, tests, observations, and documentation. Data analysis techniques included qualitative and quantitative data analysis. The action achievement indicator was set at 70%. The results of the study showed that using the PBL (Problem-Based Learning) model with picture card media could improve students' reading skills. Reading ability increased with an average score of 59.2 in cycle I (low category) and an average of 79.3 (high category) in cycle II. Therefore, the use of picture cards with the PBL model is recommended for teachers in conducting reading instruction.